1973
DOI: 10.1007/bf02641797
|View full text |Cite
|
Sign up to set email alerts
|

Application of partial hydrogenation theory to the design of commercial reactors for hydrogenating triglyceride oils

Abstract: Within the last 15-20 years, major advances have been publicized regarding the mechanism and general understanding of the partial hydrogenation of triglycerides, including soybean off, cottonseed oil, corn oil and various animal fats (primarily hog and beef fats). Although edible shortenings, oleomargarine stocks and soap stocks are produced in large quantities, there is considerable doubt that the theory and fundamental information relative to hydrogenation is always applied to the fullest extent in designing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1975
1975
2000
2000

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…A recent extensive review by Veldsink et al, however, showed that no intrinsic, explicit kinetic model is available. Moreover, Albright, Bern et al, Marangonzis et al and Chen et al reported that mass transfer is the rate-limiting step in most of the commercial reactors. As can be seen in Table , the majority of the authors measured the volumetric mass-transfer coefficient, k L a , by recording of the rate of change of the iodine value, , by a chemical method, , and by a physical method using a hydrogen probe .…”
Section: Introductionmentioning
confidence: 99%
“…A recent extensive review by Veldsink et al, however, showed that no intrinsic, explicit kinetic model is available. Moreover, Albright, Bern et al, Marangonzis et al and Chen et al reported that mass transfer is the rate-limiting step in most of the commercial reactors. As can be seen in Table , the majority of the authors measured the volumetric mass-transfer coefficient, k L a , by recording of the rate of change of the iodine value, , by a chemical method, , and by a physical method using a hydrogen probe .…”
Section: Introductionmentioning
confidence: 99%
“…Wisniak e Albright (1961) explicam que a causa provável para este período de indução seja a adsorção de seletiva de impurezas ao catalisador, como hidroperóxidos e substâncias que geram cor, que além de reduzirem o número de sítios ativos, hidrogenam lentamente. Dessa forma, o catalisador necessitará de um tempo inicial ou de indução para retomar toda sua atividade catalítica, conforme afirmam Albright (1973), Patterson (1983), Hashimoto et al (1971). Esse tempo de indução foi determinado de acordo com os gráficos apresentados na figura 4.2.…”
Section: Equações Diferenciais De Conservação Da Massaunclassified